2015
DOI: 10.1016/j.apergo.2015.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Managing children's postural risk when using mobile technology at home: Challenges and strategies

Abstract: Maintaining the musculoskeletal health of children using mobile information and communication technologies (ICT) at home presents a challenge. The physical environment influences postures during ICT use and can contribute to musculoskeletal complaints. Few studies have assessed postures of children using ICT in home environments. The present study investigated the Rapid Upper Limb Assessment (RULA) scores determined by 16 novice and 16 experienced raters. Each rater viewed 11 videotaped scenarios of a child us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 39 publications
0
10
0
1
Order By: Relevance
“…We speculate that the increased use of the thumb's proximal degrees of freedom (i.e., CMC and MCP joints) rather than the IP joint, and the less extended posture of the wrist, may represent a preferred posture for the user. Further studies should assess whether the increased use of the thumb's proximal degrees of freedom relative to the distal joint is associated with a reduced incidence of musculoskeletal disorders such as osteoarthritis and tendinitis, as several case studies have been reported in relation to the use of mobile devices (Menz, 2005;Ming et al, 2006;Storr et al, 2007;Ciccarelli et al, 2015;Ashurst et al, 2010).…”
Section: Discussionmentioning
confidence: 96%
“…We speculate that the increased use of the thumb's proximal degrees of freedom (i.e., CMC and MCP joints) rather than the IP joint, and the less extended posture of the wrist, may represent a preferred posture for the user. Further studies should assess whether the increased use of the thumb's proximal degrees of freedom relative to the distal joint is associated with a reduced incidence of musculoskeletal disorders such as osteoarthritis and tendinitis, as several case studies have been reported in relation to the use of mobile devices (Menz, 2005;Ming et al, 2006;Storr et al, 2007;Ciccarelli et al, 2015;Ashurst et al, 2010).…”
Section: Discussionmentioning
confidence: 96%
“…on the floor) and a variety of postures at those workstations (e.g. side lying, prone lying, cross-legged sitting) [ 16 , 73 ], along with the resulting musculoskeletal consequences, are yet to be studied.…”
Section: Discussionmentioning
confidence: 99%
“…This study contributes several findings with possible practical importance to touchscreen interface design. There is great variability of postures when using touchscreen mobile computing devices (Ciccarelli et al , 2015, Gold, Driban, 2012. Moreover, there is currently limited knowledge of important factors such as muscle activity for even the most common postures (Kietrys et al , 2015).…”
Section: Discussionmentioning
confidence: 99%